Plant growth and total Nitrogen absorption rate in leachate with water hyacinth (Eichhornia crassipes) - Dyah Wahyu Wijayanti; Wahyudi Budi Sediawan; Agus Prasetya (Center for Science and Technology, IAIN Surakarta, 2019)
Phytoremediation is a simple technique of wastewater processing by utilizing the plant activity to vanish, replace and stabilize or destroy the pollutant either organic compound or inorganic. This research utilizes Eichhornia crassipes as the biofilter in handling the leachate produced from organic waste degradation. The purposes of this research are to find out the plant growth rate and total Nitrogen (N) absorption in leachate by the Eichhornia crassipes. The experiment shows that the concentration of leachate affects the absorption rate of total N and wet weight of the plant. The model was fit to the experimental data. The metabolism reaction rate constant ( ) and absorption rate constant ( ) at leachate concentration 5%, 10%, 15%, 20%, 25% and 30% were measured. The highest reaction rate constant and absorption rate constant were 5% of leachate concentration where = 0.008042/day and = 2.30811/day, whilst at the leachate concentration of 30% reaction rate constant and absorption rate constant were the lowest where it reached = 0.00029/day and = 0.04576/day. The absorption ability of water hyacinth to absorb the N which contained in the leachate was affected by the metabolism reaction rate of nitrogen in the plant and the reaction rate of nitrogen degradation into ammonia (NH4) and nitric ion (NO3) in the plant root. The leachate concentration affected the efficiency of N absorption by the water hyacinth. The efficiency of N absorption at leachate concentration of 5; 10; 15; 20; 25 and 30 were 89.81%, 68.99%, 49.51%, 36.32%, 30.28% and 21.64% respectively. Overall, this technique presents a simple technique approach and the utilization of elements contained in the leachate as the nutrition for plant.